2000
DOI: 10.1046/j.1365-2923.2000.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of undergraduate students' written English language skills

Abstract: This study was useful in providing a means to objectively rate students' written English language skills and to target students in need of formative feedback and tuition. However, further research is necessary for both evaluation of medical writing and interventions for its improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The ethnic minority students scored higher on impersonal attitude, suggesting that they integrate less of the patients’ background and the patients’ perspective into history taking. Another study found that non-native English speakers in Australia scored significantly lower than native English speaking students on appropriate content and appropriate use of the English language for a writing skills assessment (Chur-Hansen and Vernon-Roberts 2000). Nevertheless, further research is required into explanations for the underperformance of ethnic minority students in the clinical and writing skills examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnic minority students scored higher on impersonal attitude, suggesting that they integrate less of the patients’ background and the patients’ perspective into history taking. Another study found that non-native English speakers in Australia scored significantly lower than native English speaking students on appropriate content and appropriate use of the English language for a writing skills assessment (Chur-Hansen and Vernon-Roberts 2000). Nevertheless, further research is required into explanations for the underperformance of ethnic minority students in the clinical and writing skills examinations.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative analysis of nursing school admission essays demonstrated that essays could differentiate between students who would complete their studies from those who would not, and that the essay question was a better predictor than measures of prior academic performance [10]. It has also been suggested that writing skills should be included in admissions processes because they are an essential part of healthcare education and practice [11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…These skills are rarely taught in a formal capacity during medical school, but are well assessed by an evaluation of a written practical assignment. 1 Research has shown that when writing skills are taught within medical schools, students demonstrate improved knowledge and overall performance. 2 The purpose of this study was to evaluate Family Medicine (FM) Clerkship students’ writing skills using an anchored scoring rubric.…”
Section: Introductionmentioning
confidence: 99%